Masalah Psikologi Siswa dalam Perspektif Islam: Antara Penyakit Hati dan Solusi Spiritual - Cut Wima Umiana Wima; Mu’alimin Mu’alimin; Mukaffan Mukaffan (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2025)
This study examines students' psychological problems from an Islamic perspective, placing heart disease as the root of the problem and spiritual solutions as the primary approach to treatment. Various psychological problems experienced by students, such as anxiety, academic stress, low self-confidence, impaired emotional regulation, and social problems, are understood not only as psychological disorders but also as manifestations of spiritual and moral imbalance. This study uses a qualitative method with a library study approach through analysis of current literature relevant to Islamic psychology, Islamic counseling, and student mental health. The results of the study indicate that the integration of modern psychology with an Islamic spiritual approach through Islamic counseling, worship practices, tazkiyah an-nafs (religious devotion), and moral development can increase psychological resilience, reduce anxiety and stress levels, and strengthen students' mental and spiritual well-being. Teachers have a strategic role as Islamic counselors in building a holistic, balanced educational environment oriented towards the development of students' mental health and character.